If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -5) = 5(x + 2) Reorder the terms: 3(-5 + x) = 5(x + 2) (-5 * 3 + x * 3) = 5(x + 2) (-15 + 3x) = 5(x + 2) Reorder the terms: -15 + 3x = 5(2 + x) -15 + 3x = (2 * 5 + x * 5) -15 + 3x = (10 + 5x) Solving -15 + 3x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -15 + 3x + -5x = 10 + 5x + -5x Combine like terms: 3x + -5x = -2x -15 + -2x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -15 + -2x = 10 + 0 -15 + -2x = 10 Add '15' to each side of the equation. -15 + 15 + -2x = 10 + 15 Combine like terms: -15 + 15 = 0 0 + -2x = 10 + 15 -2x = 10 + 15 Combine like terms: 10 + 15 = 25 -2x = 25 Divide each side by '-2'. x = -12.5 Simplifying x = -12.5
| 3(-5x+40)+8=0 | | (14)/(5x^(2/3))*(2x^3) | | 4(9x+3)+2(12-x)= | | x+38=2(x+10)+4 | | 72x-44=45 | | 16=u/2 | | 0.06+2(0.07x-1)=2 | | 8x+8x+8x=143 | | -8=5n | | 7X+6x-3x-5=25 | | 10(x+2)=4(x-1) | | x^2-31x+130=0 | | 10-32=56 | | 266=-14a | | x+5y=6x+15 | | 8p=-4 | | -11+-5+-4= | | 2(x-3)-10=14 | | 72+n=78 | | -(-5/3x3) | | 30=15z | | X+18=3(2x+1) | | 7(2+3x)+12= | | 6h-3.7h= | | (9+6n)+(-5+9m)= | | N*-3+8=20 | | 5x^2-28=17 | | 3(x+4)+12=48 | | -4a-2(-6a+2)=-22 | | 7(-10-3x)=-28 | | -k^4+3k^3+9k^2+5k=0 | | -4+3y=4 |